Pelatihan Media Pembelajaran Interaktif Berbantuan Geogebra Pada Pembelajaran Matematika - Dewi Anggreini; Sukiyanto Sukiyanto; Denik Agustito; Annis Deshinta Ayuningtyas (IKIP PGRI Bojonegoro, 2023)
ABSTRACTLearning mathematics is considered difficult material by students from elementary school to high school. Based on the results of observations made through interviews with Mathematics teachers, it was found that the problems experienced by students at SMAN 1 Sewon Bantul were found. The problems experienced by students are related to three dimensions and geometry transformation materials. In addition, there are still many students who cannot understand and visualize geometry material. How to make it easier to learn and understand abstract mathematics, especially geometry material, requires learning media, namely mathematics software. In learning mathematics, students need technology-based media that can represent their intuition in understanding a mathematical concept. The purpose of this service is to socialize GeoGebra Android as an open-source application to visualize geometry learning very accurately and more easily for high school students. The method used in this service activity is a training method through lectures, discussions, demonstrations, and assignments. With the use of applications in learning, it is expected to increase students' motivation and understanding in learning mathematics, especially geometry material. The results of the questionnaire from 24 respondents of class XII IPA 6 students obtained a percentage that as much as 72.7% agreed that learning using geogebra was very interesting and interactive in learning geometry material. Keywords: GeoGebra, geometry, training, math learning. ABSTRAKPembelajaran matematika dianggap materi yang sulit bagi para siswa. Didasari dari hasil observasi yang sudah dilakukan melalui wawancara bersama guru mata pelajaran Matematika ditemukan permasalahan yang dialami siswa di SMAN 1 Sewon Bantul. Permasalahan yang dialami oleh siswa yaitu terkait dimensi tiga dan materi transformasi geometri. Selain itu, siswa belum dapat memahami dan menvisualisasikan materi geometri. Cara mempermudah belajar dan memahami matematika yang abstrak khususnya materi geometri diperlukan media pembelajaran yaitu software matematika. Dengan demikian pada pembelajaran matematika, diperlukan suatu media berbasis teknologi yang dapat membantu siswa dalam memahami konsep matematika. Sehingga tujuan dari pengabdian untuk mensosialisasikan GeoGebra Android sebagai aplikasi open source untuk memvisualisasikan pembelajaran geometri dengan sangat akurat dan lebih mudah bagi siswa SMA. Metode yang digunakan dalam kegiatan pengabdian ini adalah metode pelatihan melalui ceramah, diskusi, demonstrasi, dan penugasan. Dengan penggunaan aplikasi dalam pembelajaran diharapkan dapat meningkatkan motivasi dan pemahaman siswa dalam pembelajaran matematika khususnya materi geometri. Hasil angket dari 24 responden siswa kelas XII IPA 6 didapatkan prosentase bahwa sebanyak 72,7% menyatakan setuju bahwa pembelajaran menggunakan geogebra sangat menarik dan interaktif dalam pembelajaran materi geometri.Kata Kunci: GeoGebra, geometri, pelatihan, pembelajaran matematika